Network Technologies for Learning Foreign Languages - Agzamkhodzhaeva Saodatxon Abrarovna (Genius Journals, 2021)
To date, a significant number of studies are devoted to communication on the Internet. Most of these works are aimed at determining the characteristics of electronic communication, its connections with other spheres of human communication, identifying genre specificity, etc. It is also noteworthy that the works carried out on the material of the English language occupy a dominant position in the total volume of research devoted to this topic.
Keywords: Network technologies; computer; electronic communication; human communication